CHANGES IN PB, CR AND CU CONCENTRATIONS IN SOME BIOINDICATORS DEPENDING ON TRAFFIC DENSITY ON THE BASIS OF SPECIES AND ORGANS - Sevik, H.; Cetin, M.; Ozturk, A.; Özel, Halil Barış; Pinar, B. (ALOKI Ltd, 2019)
The growing population and industrialization is causing air pollution. In some cities pollution has reached to a point where it is threatening human lives. Pollution has become one of the biggest issues of today's world. Pollutants are produced by exhaust gases, car wheels, and vehicles. Heavy metals (HM) are one of the major culprits that cause air pollution. This is due to the fact that HM can exist in the environment for a long time without deterioration, and their concentration in the atmosphere is ever-growing. They also tend to bioaccumulate. Therefore, determining HM concentration levels is crucial in terms of identifying risk zones and levels. Bioindicators are the most important determinants that can indicate the change in the concentration of HM in the atmosphere. This study aims to monitor the changes in Pb, Cr and Cu concentrations in the leaves, seeds and branches of cherry plum (Prunus ceracifera), horse chestnut (Aesculus hippocastanum), Tilia (Tilia tomentosa), European ash (Fraxinus excelsior) and Norway maple (Acer platanoides) species, which can be used for monitoring the traffic-induced HM concentration. We observed that the concentration of all the elements increased according to the traffic density, this is especially visible in the case of Pb and Cr.
Keywords: Landscape Plant; Heavy Metal; Urban Road; Biomonitoring; Plant Species; Pollution; Vehicle; Agronomy and Crop Science